2022
DOI: 10.1002/ijfe.2660
|View full text |Cite
|
Sign up to set email alerts
|

Stock markets response to contagious disease: Evidence on the impact of COVID‐19 in the three worst hit African economies

Abstract: This study analyses whether Coronavirus health shocks and government responses in terms of lockdown policy and stringency measures impact stock markets in Africa. We found that stock markets appeared to be more negatively responsive to growth in total number of COVID‐19 reported cases than the growth in deaths in the case of Nigeria and South Africa. While for Egypt, the stock market reacted significantly negative to both COVID‐19‐related indicators. Our results further show that government stringency policy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…There is also biasedness in the convergence of OLS when we have infinite samples; (b) there are high chances of autocorrelation and heteroscedasticity occurring from OLS estimates given that omitted dynamics are accounted for by the error term, which invalidate inferences from the normal tables. Hence, the z -statistics are unreliable for the OLS estimates; and (c) another advantage is that these models deal with the issue of endogeneity (Iqbal et al, 2020; Kumeka & Adeniyi, 2022). Further, these techniques provide consistent and efficient estimation of the vector of cointegration and do not suffer from serial correlation and simultaneity biases.…”
Section: Data Model Specification and Econometric Approachmentioning
confidence: 99%
“…There is also biasedness in the convergence of OLS when we have infinite samples; (b) there are high chances of autocorrelation and heteroscedasticity occurring from OLS estimates given that omitted dynamics are accounted for by the error term, which invalidate inferences from the normal tables. Hence, the z -statistics are unreliable for the OLS estimates; and (c) another advantage is that these models deal with the issue of endogeneity (Iqbal et al, 2020; Kumeka & Adeniyi, 2022). Further, these techniques provide consistent and efficient estimation of the vector of cointegration and do not suffer from serial correlation and simultaneity biases.…”
Section: Data Model Specification and Econometric Approachmentioning
confidence: 99%
“…Kumeka et al employed three cointegrating regression models to study the stock markets in the three African economies, Nigeria, South Africa, and Egypt, which were hardest hit by COVID-19 and strict lockdown policies [27]. The increase in new diagnoses and the number of daily deaths negatively impacted the stock markets of the three countries [27].…”
Section: Africamentioning
confidence: 99%
“…Kumeka et al employed three cointegrating regression models to study the stock markets in the three African economies, Nigeria, South Africa, and Egypt, which were hardest hit by COVID-19 and strict lockdown policies [27]. The increase in new diagnoses and the number of daily deaths negatively impacted the stock markets of the three countries [27]. Furthermore, they discovered that returns were more responsive to the overall increased reported cases per day and the stringency policy than the increase in mortality in Nigeria [27].…”
Section: Africamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Xu (2021) provides evidence that increased COVID-19 cases has a negative effect on stock returns in the United States and Canada. Kumeka and Adeniyi (2022) found that stock markets appeared to be more negatively responsive to growth in total number of COVID-19 reported cases than the growth in deaths in the case of Nigeria and South Africa. Using U.S. data, Hsu and Liao (2021) show that COVID-19 has a positive effect on stock price volatility and trading volume and that it is negatively associated with stock returns.…”
Section: Introductionmentioning
confidence: 95%